Absorption of CO2 in Biogas with Amine Solution for Biomethane Enrichment - Kamopas, Wassana; Asanakham, Attakorn; Kiatsiriroat, Tanongkiat (Journal of Engineering and Technological Sciences, 2016)
Biogas upgrading with carbon dioxide absorption in a column of monoethanolamine (MEA) solution was carried out. The effects of controlled parameters on the CO2 absorption such as gas flow rate, solution concentration, height to diameter ratio of the column were considered. High CH4 concentration could be achieved at low gas flow rate and high MEA concentration. The CH4 concentration could be up from 70-75% to 92-95% by volume for 0.2 M MEA. A set of breakthrough curves was obtained to determine the absorption characteristics, such as the absorption constant (k), the absorption time when the CO2 concentration at the outlet was 50% of the concentration at the inlet (t), and the absorption period (t*) when the CH4 concentration was over 90%. An empirical equation of the methane enrichment with the related parameters was developed.